2020
DOI: 10.20944/preprints202008.0435.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term Use of a Sensory Neuroprosthesis Improves Function in a Patient with Peripheral Neuropathy: a Case Report

Abstract: Background:Peripheral neuropathy (PN) can result in either partial or complete loss of distal sensation resulting in an increased fall risk. Walkasins® uses a shoe insert to detect the magnitude and direction of sway and sends signals to a leg unit that provides sensory balance cues. The objective of this case report is to describe the long-term influence of the Walkasins® lower limb sensory neuroprosthesis on balance and gait for an individual with diabetic PN.Case Description:A fifty-one-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 57 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…Consequently, we hypothesize that any balance-related therapy or training activity in conjunction with wearing the device would provide an additive effect to overall function and balance outcomes. This hypothesis is supported by our recent case study (Wrisley et al, 2018(Wrisley et al, , 2020 as well as our previous inclinic study where subjects following a baseline assessment were randomized to either wearing the device turned on or turned off while performing a brief 10-15 min standardized balance activity session with a physical therapist (Koehler-McNicholas et al, 2019). Ten of 15 subjects in the on group increased their FGA scores by at least 4 points compared to five of 16 in the off group (p < 0.05).…”
Section: Physical Intervention Versus Sensory Substitutionsupporting
confidence: 75%
See 3 more Smart Citations
“…Consequently, we hypothesize that any balance-related therapy or training activity in conjunction with wearing the device would provide an additive effect to overall function and balance outcomes. This hypothesis is supported by our recent case study (Wrisley et al, 2018(Wrisley et al, , 2020 as well as our previous inclinic study where subjects following a baseline assessment were randomized to either wearing the device turned on or turned off while performing a brief 10-15 min standardized balance activity session with a physical therapist (Koehler-McNicholas et al, 2019). Ten of 15 subjects in the on group increased their FGA scores by at least 4 points compared to five of 16 in the off group (p < 0.05).…”
Section: Physical Intervention Versus Sensory Substitutionsupporting
confidence: 75%
“…Other wearable neuromodulation technologies have been used as a treatment modality in a home setting, although typically only worn in conjunction with a home therapy program for balance and mobility in different categories of subjects, e.g., multiple sclerosis (Leonard et al, 2017) and healthy elderly (Bao et al, 2018). A recent case study of a patient with PN wearing Walkasins for a year (Wrisley et al, 2018(Wrisley et al, , 2020, found dramatic improvements in gait and balance outcomes when daily continuous device use was combined with balance therapy. Prior to using Walkasins, the patient had received balance therapy twice a week for over 5 months by an expert physical therapist (DW) and had plateaued in his improvements (Wrisley et al, 2018(Wrisley et al, , 2020).…”
Section: Physical Intervention Versus Sensory Substitutionmentioning
confidence: 99%
See 2 more Smart Citations